MTsS Kluet Utara Aceh Selatan تحسين اللهجة اللغوية باستخدام وسيلة فيديو بـ - Amaliah, Zarinatul; Idris, Aisyah; Fajriah, Fajriah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2022)
Based on the result of the observation in grade 1 at MTsS Kluet Utara, the researcher found that the majority of the students were difficult to communicate in Arabic language. The difficulties are not only about the pronounciations but also Arabic alphabets, words, and sentences. In fact, they speak Arabic by using the Indonesian dialect. The aims of this study were to know the effectiveness of the video media used to improve students’ Arabic dialect. This observation is also to know the activities of the teachers and the students in the implementation of the video media. The researcher applied the pre-experimental method through one group pre -test post –test design. To collect the data, the researcher used the observation sheets and provided pre and post-tests to the students. The findings of the study were that the T-test was higher than T-table (4,20 <2,07<2,78). Furthermore, the observation showed that the teachers’ activities in using the video to improve the language dialect were very good scores (88%) after the implementation of the media. In accordance with the teachers, the students’ achievement were also very good (85%).